Software Process Improvement: It's a Journey, Not a Destination. - Hardgrave, Bill C.; Armstrong, Deborah J. (Communications of the ACM, 2005)
Presents the authors' opinion on the benefits of continuous software process improvement. Efforts made by AA Corp. to improve its software development processes; Adoption of the Capability Maturity Model for guidance; Start of software process improvement initiative at AA Corp.